Correlation of retinal nerve fibre layer and macular thickness with serum uric acid among type 2 diabetes mellitus - Naidu, Vinuthinee Naidu A/P Munisamy (2016)
Background Serum uric acid is a final breakdown product of purine catabolism in humans. It’s a potent antioxidant, that induces oxidative stress on the vascular endothelial cells, thus mediating progression of diabetic related diseases. Various epidemiological and experimental evidence suggest that uric acid has a role in the etiology of type 2 diabetes mellitus. We conducted a cross-sectional study to evaluate the correlation of RNFL and macular thickness with serum uric acid in type 2 diabetic patients. Methodology A cross-sectional study was conducted in the Eye Clinic, Hospital Universiti Sains Malaysia, Kelantan between the period of August 2013 till July 2015 involving type 2 diabetes mellitus patients with no diabetic retinopathy and with NPDR. An evaluation for RNFL and macular thickness using Spectralis Heidelberg optical coherence tomography was done and 6 mls of venous blood was taken for the measurement of serum uric acid and HbA1C. Results A total of 180 diabetic patients were recruited (no diabetic retinopathy: 90 patients and NPDR: 90 patients) into the study. The mean level of serum uric acid for both the groups were within normal range and there was no significance difference between the two groups. The mean level of serum uric acid for both gender was significantly higher in no diabetic retinopathy group (p = 0.004 respectively). The mean serum uric acid was significantly higher in patient with HbA1C < 6.5% (p < 0.031). Patients with NPDR have thicker RNFL and macular thickness comparedto patient with no diabetic retinopathy. However, only the RNFL thickness of the temporal quadrant and the macular thickness of the superior outer, inferior outer and temporal outer subfields were statistically significant (p = 0.038, p = 0.004, 0.033 and <0.001 respectively). There was poor correlation between RNFL and macular thickness with serum uric acid in both the groups. Conclusion Serum uric acid showed a poor correlation with RNFL and macular thickness among type 2 diabetic patients.